Preparation method of Cu-SSZ-13 molecular sieve and application of molecular sieve

By introducing vitamin C in the preparation process of Cu-SSZ-13 molecular sieve, Cu-SSZ-13 molecular sieve with larger micropore volume and specific surface area was prepared, which solved the shortcomings of the existing Cu-SSZ-13 molecular sieve in terms of catalytic performance, anti-sulfur poisoning and hydrothermal stability, and achieved more efficient NH3-SCR catalytic reaction performance.

CN120004287AInactive Publication Date: 2025-05-16CHANGCHUN UNIV OF SCI & TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510486560.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-18
Publication Date
2025-05-16
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing Cu-SSZ-13 molecular sieves have shortcomings in catalytic performance, anti-sulfur poisoning and hydrothermal stability, especially in low-temperature catalytic activity and high-temperature denitrification performance.

Method used

During the preparation of Cu-SSZ-13 molecular sieve, vitamin C was introduced as a modifier, and Cu-SSZ-13 molecular sieve with a larger micropore volume and specific surface area was prepared through hydrothermal crystallization and ion exchange reaction.

Benefits of technology

The catalytic activity, hydrothermal stability and anti-sulfur poisoning ability of Cu-SSZ-13 molecular sieve in NH3-SCR reaction has been significantly improved, and it meets stricter exhaust emission standards. It is simple in preparation, cost-economic and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120004287A_ABST
    Figure CN120004287A_ABST
Patent Text Reader

Abstract

The invention relates to the field of catalytic chemistry, in particular to a preparation method of a Cu-SSZ-13 molecular sieve and application of the molecular sieve.The preparation method comprises the following steps that an aluminum source, a silicon source, inorganic alkali, an organic structure-directing agent, water and Vc are sequentially mixed to form gel, the gel is stirred, aging treatment is conducted, and aged gel is obtained; continuously crystallizing in a high-pressure kettle to obtain a crystallized product; filtering, washing, drying and calcining; and performing ion exchange with copper salt to obtain a finished product. The additive Vc is added, the preparation method is simple, the cost is low, the synthesis environment is friendly, and secondary pollution is avoided; after Vc modification, the microporous structure and the specific surface area of the finished product are obviously increased; according to the finished product, the NH3-SCR catalytic performance is improved, the catalyst has very excellent catalytic activity and a wide temperature window, and the hydrothermal aging resistance and the sulfur poisoning resistance of the catalyst are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of catalytic chemistry, and in particular to a method for preparing a Cu-SSZ-13 molecular sieve and application of the molecular sieve. Background Art

[0002] In view of the increasing attention paid to environmental protection and the continuous optimization and adjustment of energy structure, automobile exhaust emission standards are becoming more and more stringent. In this context, the market demand for efficient and environmentally friendly catalytic materials is showing a rapid growth trend. Molecular sieves, with their unique pore structure and adjustable acidic properties, have shown great application potential and broad application prospects in the field of catalysis. In particular, Cu-SSZ-13 molecular sieve, as an efficient ammonia selective catalytic reduction (NH3-SCR) catalyst, is used in the NO removal of mobile sources such as diesel vehicles. x It has received extensive attention and application in exhaust gas catalytic purification (Shan Wenpo et al., Environmental Science Research 2019; Chen et al., Fuel 2023). However, the currently prepared Cu-SSZ-13 still has many limitations and shortcomings in its application, such as the catalytic performance needs to be improved (insufficient low-temperature catalytic activity, narrow temperature window, etc.), poor sulfur resistance and stability, etc. Researchers have been improving the preparation process such as hydrothermal crystallization and post-treatment to improve the catalytic performance of Cu-SSZ-13.

[0003] In the application with patent number CN202211572427.X, cyclohexylamine and N,N,N-trimethyl-1-adamantyl ammonium hydroxide are used as templates, Y zeolite is used as silicon source and aluminum source, and Cu-SSZ-13 molecular sieve is prepared by hydrothermal crystallization and ion exchange reaction. Cyclohexylamine is used as a common template in this application, which saves the synthesis cost and is suitable for NO at higher temperature. x Conversion, but the low-temperature catalytic performance is improved little. In the application with patent number CN202410840273.0, water, alkali source, silicon source, aluminum source, and vanadium activator are used for crystallization, and then ion exchange is performed to obtain a spherical Cu-SSZ-13 molecular sieve with a large specific surface area. In this application, the low-temperature catalytic activity and hydrothermal stability are significantly improved, but the high-temperature denitrification performance and anti-sulfur poisoning performance are insufficient, and the addition of vanadium activators has certain environmental hazards. Summary of the invention

[0004] In order to overcome the shortcomings of the above-mentioned prior art, the core goal of the present invention is to synthesize Cu-SSZ-13 molecular sieves with larger micropore volume and specific surface area by introducing a certain amount of environmentally friendly vitamin C (Vc) as a modifier during the preparation of Cu-SSZ-13 molecular sieves to enhance their catalytic performance, sulfur poisoning resistance and hydrothermal stability in the ammonia selective catalytic reduction (NH3-SCR) reaction. Through this innovative modification method, the present invention aims to achieve the performance improvement of Cu-SSZ-13 molecular sieves in NH3-SCR reactions to meet more stringent exhaust emission standards, while contributing to environmental protection and energy conservation.

[0005] To achieve the above object, the present invention provides the following technical solutions: A method for preparing a Cu-SSZ-13 molecular sieve comprises the following steps: (1) mixing an aluminum source, a silicon source, an inorganic base, an organic structure directing agent, water and vitamin C in sequence, wherein the molar ratio of the aluminum source, the silicon source, the inorganic base, the organic structure directing agent, water and vitamin C is 1: 30-50: 15-18: 3-10: 500-1500: 0.3-5, to form a gel, stirring the gel for a period of time at room temperature, and performing an aging treatment to obtain an aged gel; (2) placing the aged gel in an autoclave for continuous crystallization for a period of time to obtain a crystallized product; filtering, washing, drying and calcining the crystallized product to obtain SSZ-13 molecular sieve; (3) The SSZ-13 molecular sieve obtained in the previous step is subjected to ion exchange with copper salt, washed, dried and calcined to obtain a finished product, namely Cu-SSZ-13 molecular sieve.

[0006] As a further solution of the present invention: the silicon source is selected from at least one of tetraethyl silicate, silica sol and white carbon black, with silica sol being preferred; the aluminum source is selected from at least one of aluminum oxide, aluminum hydroxide, aluminum sulfate and aluminum nitrate, with aluminum sulfate being preferred; the inorganic base is preferably sodium hydroxide; the organic structure directing agent is N,N,N-trimethyladamantane ammonium hydroxide; the copper salt is one of copper nitrate, copper acetate and copper sulfate, with copper nitrate being preferred; and vitamin C is preferably selected with a mass percentage of more than 95% Vc.

[0007] As a further solution of the present invention: the stirring speed is 50-300 r / min, preferably 100-200 r / min.

[0008] As a further solution of the present invention: the aging temperature is 10-40° C., preferably 20-30° C.; the aging time is 3-8 hours, preferably 3-5 hours.

[0009] As a further solution of the present invention: the crystallization temperature is 110-170° C., preferably 110-140° C.; the crystallization time is 3-7 days, preferably 4-6 days.

[0010] As a further solution of the present invention: the drying temperature is 80-150° C., preferably 100-110° C.; the drying time is 8-16 hours, preferably 10-14 hours; the calcination temperature is between 300-700° C., preferably 500-600° C.; the calcination time is between 2-10 hours, preferably 3-5 hours.

[0011] As a further solution of the present invention: the temperature of the ion exchange is 25-85°C, preferably 80°C; the concentration of the copper salt is 0.002-0.2 mol / L, preferably 0.005 mol / L.

[0012] An application of a finished product prepared by the above-mentioned Cu-SSZ-13 molecular sieve preparation method in NH3-SCR catalytic reaction. The finished product obtained by the method of the present invention has a CHA-type topological structure, and the catalyst has good denitration performance. When the reaction temperature is in the range of 180-500°C, the conversion rate of NO is above 90%. It has good resistance to hydrothermal aging and sulfur poisoning.

[0013] Compared with the prior art, the present invention has the following beneficial effects: (1) Adding vitamin C during the crystallization process significantly increases the microporous structure and specific surface area of ​​the prepared Cu-SSZ-13 molecular sieve, and significantly improves the crystallinity of the molecular sieve; (2) The Cu-SSZ-13 molecular sieve prepared by Vc modification has improved NH3-SCR catalytic activity, hydrothermal stability and resistance to sulfur poisoning, and has broad application prospects in the purification of nitrogen oxide exhaust from diesel vehicles.

[0014] (3) The present application adopts the method of adding vitamin C during the crystallization process to prepare Cu-SSZ-13 molecular sieve. The preparation method is simple, cost-effective, and the synthesis process is environmentally friendly without secondary pollution. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 The X-ray diffraction (XRD) diagrams of the molecular sieves obtained in Examples 1-10 and Comparative Example 1 of the present invention are shown in Figures 1-10 and 1-1. ak corresponds to Examples 1-10 and Comparative Example 1, respectively.

[0016] Figure 2 The N2 adsorption-desorption isotherm (A) and pore size distribution curve (B) of the molecular sieves obtained in Examples 1-10 and Comparative Example 1 of the present invention are shown in Table 1. ak corresponds to Examples 1-10 and Comparative Example 1, respectively.

[0017] Figure 3 The following are scanning electron microscope (SEM) images of the molecular sieves obtained in Example 1 and Comparative Example 1 of the present invention. a and b are Comparative Example 1, and c and d are Example 1.

[0018] Figure 4 For Example 1 of the present invention and Comparative Example 1 27 Al NMR spectrum.

[0019] Figure 5 The graph is a graph showing the NO conversion rate of the molecular sieves obtained in Examples 1-9 of the present invention and Comparative Example 1 in the NH3-SCR catalytic reaction as a function of temperature.

[0020] Figure 6 The graph is a graph showing the NO conversion rate of the molecular sieves obtained in Examples 11-12 of the present invention and Comparative Example 2 in the NH3-SCR catalytic reaction as a function of temperature.

[0021] Figure 7 The graph is a graph showing the NO conversion rate versus temperature of the molecular sieves obtained in Examples 1-2 of the present invention and Comparative Example 1 in an NH3-SCR catalytic reaction in the presence of 100 ppm SO2. DETAILED DESCRIPTION

[0022] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] The method of the present invention introduces Vc as a modifier during the synthesis of the molecular sieve. Through this innovative addition step, the specific surface area and pore structure of the molecular sieve can be significantly optimized, the crystallinity of the molecular sieve can be significantly improved, and it can be applied to the NH3-SCR catalytic reaction, thereby improving the reaction efficiency.

[0024] In the context of this specification, XRD is measured by a D8 Advance polycrystalline X-ray powder diffractometer, using a Cu-Kα ray source, a Kα1 wavelength voltage of 40 kV, a current of 100 mA, a nickel filter, a scanning angle 2θ of 5 to 50°, and a scanning rate of 1° / min.

[0025] In the context of this specification, the N2 adsorption-desorption isotherm of the catalyst is determined by a specific surface area and porosity analyzer. The specific surface area and porosity analyzer of the catalyst are tested and analyzed by an Autosorb-iQ physical adsorption instrument. The specific surface area is analyzed by the BET method, and the pore size distribution is analyzed by the NLDFT method.

[0026] In the context of this specification, the catalytic activity of the catalyst NH3-SCR reaction is evaluated by a gas-solid phase catalytic reaction fixed bed reactor test. The obtained molecular screening was evaluated for the selective catalytic reduction of nitrogen oxides by ammonia using samples with a size of 40-80 mesh on a fixed bed reactor with an inner diameter of 10 mm and a length of 400 mm. The gas simulating the exhaust composition contained N2, O2, NH3 and NO, wherein N2 was used as a carrier gas, [NO] = [NH3] = 500 ppm, [O2] = 5%, and the total flow rate of the reaction gas was controlled to 500 mL / min. The starting temperature and heating program of the reaction were set in the experiment, wherein the heating rate was 10 °C per minute, and the temperature range was from 100 °C to 550 °C. The concentration of the inlet and outlet gases was measured using a nitrogen oxide analyzer (Thermo model 42i-HL). The experimental device for testing SO2 poisoning performance is consistent with the above-mentioned activity evaluation device. It is necessary to add a set of SO2 gas lines, adjust the flow meter to pass 100 ppm SO2 gas, and select the reaction temperature as 300 °C. At the same time, the outlet NO concentration after the molecular sieve catalytic reaction is monitored.

[0027] Example 1: This example provides a method for preparing Cu-SSZ-13 molecular sieve by adding Vc as a modifier, which specifically includes the following operations: Take 31.65 g of N, N, N-trimethyladamantane-1-ammonium hydroxide (TMAdaOH, 25% mass fraction aqueous solution) and mix with 14.91 g of deionized water, add 4.8 g of NaOH, stir vigorously until completely uniform, then add 0.99 g of Vc, add 30 g and 2.5 g of 30% mass fraction silica sol as silicon source and aluminum sulfate 18hydrate as aluminum source, stir for 3 hours, and then obtain a milky white gel-like mixed solution. Then, the mixed solution is loaded into a reactor, and the reactor is placed in a 140℃ oven for 4 days to complete crystallization. The obtained sample is filtered and washed several times, dried at 100℃ overnight, and placed in a muffle furnace for calcination at 550℃ for 4 hours to obtain SSZ-13 molecular sieve. The SSZ-13 sample was ion exchanged with 0.1 mol / L Cu(NO3)2•3H2O solution at 80°C for 5 hours, then filtered and washed, dried at 100°C for 12 hours, and finally calcined at 550°C in a muffle furnace for 4 hours to obtain Cu-SSZ-13 molecular sieve. The molar ratio of the above aluminum source, silicon source, inorganic base, organic structure directing agent, water and Vc is 1: 40: 16: 5: 900: 1.5.

[0028] Figure 1 Contains the XRD pattern of the sample of Example 1. Figure 1It can be seen that the characteristic diffraction peaks of typical CHA structure molecular sieves appear at 2θ=9.7°, 13.2°, 14.2°, 16.4°, 17.9°, 21.1°, 25.1° and 31.1°, indicating that the sample is a pure phase Cu-SSZ-13 molecular sieve with good crystallinity. Figure 2 From the N2 adsorption and desorption and pore size distribution curves, it can be seen that the sample in Example 1 has a typical microporous structure with a pore size of about 0.38-0.39 nm. The specific surface area of ​​the sample is 714 m 2 •g -1 , the micropore volume is 0.26 cm 3 •g -1 . Figure 3 The scanning electron microscope image in the figure shows that the sample morphology is close to rod-shaped particles, with a width of 200nm, a length of 800-900nm, a smooth surface and a high degree of crystallinity. Figure 4 of 27 It can be seen from the Al NMR spectrum that the aluminum in the sample mainly exists in the tetracoordinate aluminum in the molecular sieve framework, and there is no aluminum outside the framework, which supports its good crystallinity.

[0029] Example 2: This example provides a method for preparing Cu-SSZ-13 molecular sieve by adding Vc as a modifier. The difference from Example 1 is that the added Vc content is 1 / 3 of that in Example 1. That is, 0.33 g of Vc is added, and the remaining addition amounts and procedures are the same as in Example 1, and finally a Cu-SSZ-13 molecular sieve is obtained. The molar ratio of the above aluminum source, silicon source, inorganic base, organic structure directing agent, water and Vc is 1: 40: 16: 5: 900: 0.5.

[0030] Figure 1 Contains the XRD pattern of the sample of Example 2. Figure 1 It can be seen that the characteristic diffraction peaks of typical CHA structure molecular sieves appear at 2θ=9.7°, 13.2°, 14.2°, 16.4°, 17.9°, 21.1°, 25.1° and 31.1°, indicating that the sample is a pure phase Cu-SSZ-13 molecular sieve with good crystallinity. Figure 2 It can be seen that the sample of Example 2 is a typical microporous structure with a pore size of about 0.38-0.39 nm and a specific surface area of ​​545 m 2 •g -1 , the micropore volume is 0.20 cm 3 •g -1 .

[0031] Example 3: This example provides a method for preparing Cu-SSZ-13 molecular sieve by adding Vc as a modifier. The difference from Example 1 is that the added Vc content is 4 / 3 times that of Example 1. That is, 1.32g of Vc is added, and the remaining addition amounts and procedures are the same as those of Example 1, and finally a Cu-SSZ-13 molecular sieve is obtained. The molar ratio of the above aluminum source, silicon source, inorganic base, organic structure directing agent, water and Vc is 1: 40: 16: 5: 900: 2.0.

[0032] Figure 1 Contains the XRD pattern of the sample of Example 3. Figure 1 It can be seen that the characteristic diffraction peaks of typical CHA structure molecular sieves appear at 2θ=9.7°, 13.2°, 14.2°, 16.4°, 17.9°, 21.1°, 25.1° and 31.1°, indicating that the sample is a pure phase Cu-SSZ-13 molecular sieve with good crystallinity. Figure 2 It can be seen that the sample of Example 3 is a typical microporous structure with a pore size of about 0.38-0.39 nm. The specific surface area of ​​the sample is 692 m 2 •g -1 , the micropore volume is 0.25 cm 3 •g -1 .

[0033] Example 4: This example provides a method for preparing Cu-SSZ-13 molecular sieve by adding Vc as a modifier. The difference from Example 1 is that the content of silica sol added is 3 / 4 of that in Example 1. That is, 22.5 grams of silica sol is added, and the remaining addition amounts and procedures are the same as in Example 1, and finally Cu-SSZ-13 molecular sieve is obtained. The molar ratio of the above aluminum source, silicon source, inorganic base, organic structure directing agent, water and Vc is 1: 30: 16: 5: 900: 1.5.

[0034] Figure 1 Contains the XRD pattern of the sample of Example 4. Figure 1 It can be seen that the characteristic diffraction peaks of typical CHA structure molecular sieves appear at 2θ=9.7°, 13.2°, 14.2°, 16.4°, 17.9°, 21.1°, 25.1° and 31.1°, indicating that the sample is a pure phase Cu-SSZ-13 molecular sieve with good crystallinity. Figure 2 It can be seen that the sample of Example 4 is a typical microporous structure with a pore size of about 0.38-0.39 nm. The specific surface area of ​​the sample is 686 m 2 •g -1 , the micropore volume is 0.25 cm 3 •g -1 .

[0035] Example 5: This example provides a method for preparing Cu-SSZ-13 molecular sieve by adding Vc as a modifier. The difference from Example 1 is that the content of silica sol added is 5 / 4 of that in Example 1. That is, 37.5 grams of silica sol is added, and the remaining addition amounts and procedures are the same as in Example 1, and finally Cu-SSZ-13 molecular sieve is obtained. The molar ratio of the above aluminum source, silicon source, inorganic base, organic structure directing agent, water and Vc is 1: 50: 16: 5: 900: 1.5.

[0036] Figure 1 Contains the XRD pattern of the sample of Example 5. Figure 1 It can be seen that the characteristic diffraction peaks of typical CHA structure molecular sieves appear at 2θ=9.7°, 13.2°, 14.2°, 16.4°, 17.9°, 21.1°, 25.1° and 31.1°, indicating that the sample is a pure phase Cu-SSZ-13 molecular sieve with good crystallinity. Figure 2 It can be seen that the sample of Example 5 is a typical microporous structure with a pore size of about 0.38-0.39 nm. The specific surface area of ​​the sample is 643 m 2 •g -1 , the micropore volume is 0.24 cm 3 •g -1 .

[0037] Example 6: This example provides a method for preparing Cu-SSZ-13 molecular sieve by adding Vc as a modifier. The difference from Example 1 is that the content of the organic structure directing agent added is 3 / 2 of that in Example 1. That is, 47.48 grams of N, N, N-trimethyladamantane-1-ammonium hydroxide is added, and the remaining addition amounts and procedures are the same as in Example 1, and finally a Cu-SSZ-13 molecular sieve is obtained. The molar ratio of the above aluminum source, silicon source, inorganic base, organic structure directing agent, water and Vc is: 1: 40: 16: 7.5: 900: 1.5.

[0038] Figure 1 Contains the XRD pattern of the sample of Example 6. Figure 1 It can be seen that the characteristic diffraction peaks of typical CHA structure molecular sieves appear at 2θ=9.7°, 13.2°, 14.2°, 16.4°, 17.9°, 21.1°, 25.1° and 31.1°, indicating that the sample is a pure phase Cu-SSZ-13 molecular sieve with good crystallinity. Figure 2 It can be seen that the sample of Example 6 is a typical microporous structure with a pore size of about 0.38-0.39 nm. The specific surface area of ​​the sample is 608 m 2 •g -1 , the micropore volume is 0.22 cm 3 •g -1 .

[0039] Example 7: This example provides a method for preparing Cu-SSZ-13 molecular sieve by adding Vc as a modifier. The difference from Example 1 is that the silicon source used is different, and the added silicon source is white carbon black. That is, 9 grams of white carbon black is added, and the remaining addition amounts and procedures are the same as in Example 1, and finally Cu-SSZ-13 molecular sieve is obtained. The molar ratio of the above aluminum source, silicon source, inorganic base, organic structure directing agent, water and Vc is: 1: 40: 16: 5: 900: 1.5.

[0040] Figure 1 Contains the XRD pattern of the sample of Example 7. Figure 1 It can be seen that the characteristic diffraction peaks of typical CHA structure molecular sieves appear at 2θ=9.7°, 13.2°, 14.2°, 16.4°, 17.9°, 21.1°, 25.1° and 31.1°, indicating that the sample is a pure phase Cu-SSZ-13 molecular sieve with good crystallinity. Figure 2 It can be seen that the sample of Example 7 is a typical microporous structure with a pore size of about 0.38-0.39 nm. The specific surface area of ​​the sample is 688 m 2 •g -1 , the micropore volume is 0.24 cm 3 •g -1 .

[0041] Example 8: This example provides a method for preparing Cu-SSZ-13 molecular sieve by adding Vc as a modifier. The difference from Example 1 is that the hydrothermal crystallization temperature used to synthesize the SSZ-13 molecular sieve is different. The reactor is placed in a 160°C oven for 4 days, and the remaining addition amounts and procedures are the same as in Example 1, and finally the Cu-SSZ-13 molecular sieve is obtained. The molar ratio of the above aluminum source, silicon source, inorganic base, organic structure directing agent, water and Vc is: 1: 40: 16: 5: 900: 1.5.

[0042] Figure 1 Contains the XRD pattern of the sample of Example 8. Figure 1 It can be seen that the characteristic diffraction peaks of typical CHA structure molecular sieves appear at 2θ=9.7°, 13.2°, 14.2°, 16.4°, 17.9°, 21.1°, 25.1° and 31.1°, indicating that the sample is a pure phase Cu-SSZ-13 molecular sieve with good crystallinity. Figure 2 It can be seen that the sample of Example 8 is a typical microporous structure with a pore size of about 0.38-0.39 nm. The specific surface area of ​​the sample is 704 m 2 •g -1 , the micropore volume is 0.26 cm 3 •g-1 .

[0043] Example 9: This example provides a method for preparing Cu-SSZ-13 molecular sieve by adding Vc as a modifier. The difference from Example 1 is that the copper salt used in the copper ion exchange is copper acetate, that is, 0.1 mol / L Cu(CH3COO)2·H2O, the ion exchange temperature is 30°C, and the remaining addition amounts and procedures are the same as in Example 1, and finally a Cu-SSZ-13 molecular sieve is obtained. The molar ratio of the above aluminum source, silicon source, inorganic base, organic structure directing agent, water and Vc is: 1: 40: 16: 5: 900: 1.5.

[0044] Figure 1 Contains the XRD pattern of the sample of Example 9. Figure 1 It can be seen that the characteristic diffraction peaks of typical CHA structure molecular sieves appear at 2θ=9.7°, 13.2°, 14.2°, 16.4°, 17.9°, 21.1°, 25.1° and 31.1°, indicating that the sample is a pure phase Cu-SSZ-13 molecular sieve with good crystallinity. Figure 2 It can be seen that the sample of Example 9 is a typical microporous structure with a pore size of about 0.38-0.39 nm. The specific surface area of ​​the sample is 708 m 2 •g -1 , the micropore volume is 0.26 cm 3 •g -1 .

[0045] Example 10: This example provides a method for preparing Cu-SSZ-13 molecular sieve by adding Vc as a modifier. The difference from Example 1 is that the content of the organic structure directing agent added is 1 / 2 of that in Example 1. That is, 15.83 grams of N, N, N-trimethyladamantane-1-ammonium hydroxide is added, and the remaining addition amounts and procedures are the same as in Example 1, and finally a Cu-SSZ-13 molecular sieve is obtained. The molar ratio of the above aluminum source, silicon source, inorganic base, organic structure directing agent, water and Vc is: 1: 40: 16: 2.5: 900: 1.5.

[0046] Figure 1 The XRD diagram of the sample of Example 10 is shown in Figure 1. It can be seen that the characteristic diffraction peaks of the typical CHA structure molecular sieve appear at 2θ=9.7°, 13.2°, 14.2°, 16.4°, 17.9°, 21.1°, 25.1° and 31.1°, and the characteristic diffraction peaks of the typical MOR structure molecular sieve appear at 2θ=19.6°, 22.2°, 26.2° and 27.8°, indicating that the sample is a CHA / MOR mixed crystal phase molecular sieve. Figure 2It can be seen that the sample of Example 10 is a typical microporous structure with a pore size of about 0.39-0.40 nm. The specific surface area of ​​the sample is 556 m 2 •g -1 , the micropore volume is 0.21 cm 3 •g -1 .

[0047] Comparative Example 1: This comparative example provides a method for preparing a Cu-SSZ-13 molecular sieve. The difference from Example 1 is that Vc is not added, and the rest of the preparation process is the same as Example 1, and finally a Cu-SSZ-13 molecular sieve is obtained.

[0048] Figure 1 Contains the XRD pattern of the sample of Comparative Example 1. Figure 1 It can be seen that characteristic diffraction peaks of typical CHA structure molecular sieve appear at 2θ=9.7°, 13.2°, 14.2°, 16.4°, 17.9°, 21.1°, 25.1° and 31.1°, indicating that the sample is a CHA pure phase molecular sieve, but the crystallinity is lower than that of Examples 1 to 10. Figure 2 It can be seen that the sample of comparative example 1 is a typical microporous structure with a pore size of about 0.38 nm. The specific surface area of ​​the sample is 475 m 2 •g -1 , the micropore volume is 0.17 cm 3 •g -1 , are lower than Examples 1 to 7. Figure 3 The scanning electron microscope image shows that the sample morphology of Comparative Example 1 is irregular block particles with a particle size of 200-500nm, a rough surface, and a lower degree of crystallinity than Example 1. Figure 4 The sample of Comparative Example 1 27 As shown in the Al NMR spectrum, the aluminum in the sample of Comparative Example 1 mainly exists in the tetracoordinate aluminum in the molecular sieve framework, but a small part exists in the pentacoordinate aluminum outside the framework, which supports the result that its crystallinity is lower than that of Example 1. The specific surface area and other data of Examples 1 to 10 and Comparative Example 1 are shown in Table 1.

[0049] Table 1 Specific surface area and pore structure parameters of Examples 1 to 10 and Comparative Example 1

[0050] It can be seen from the data in Table 1 that by comparing the data of Comparative Example 1 with Examples 1 to 10, it is shown that the Cu-SSZ-13 molecular sieve prepared after modification by adding vitamin C has a larger specific surface area and micropore volume.

[0051] Example 11: In this example, the Cu-SSZ-13 molecular sieve prepared above was subjected to hydrothermal aging treatment to obtain a sample after hydrothermal aging treatment, and then NH3-SCR performance was measured to evaluate its hydrothermal stability. Hydrothermal aging treatment process: The Cu-SSZ-13 molecular sieve of Example 1 was placed in a tubular furnace, and air with a mass fraction of 10% H2O was continuously introduced, and hydrothermal aging treatment was performed at 750°C for 16 hours. A sample after hydrothermal aging was obtained.

[0052] Example 12: In this example, the Cu-SSZ-13 molecular sieve prepared above is subjected to hydrothermal aging treatment to obtain a sample after hydrothermal aging treatment, and then NH3-SCR performance measurement is performed to evaluate its hydrothermal stability. This example is a sample of Example 2 subjected to hydrothermal aging treatment. The specific process is: the Cu-SSZ-13 molecular sieve of Example 2 is placed in a tubular furnace, air with a mass fraction of 10% H2O is continuously introduced, and hydrothermal aging treatment is performed at 750°C for 16 hours. A sample after hydrothermal aging is obtained.

[0053] Comparative Example 2: In this comparative example, the Cu-SSZ-13 molecular sieve prepared in Comparative Example 1 is subjected to hydrothermal aging treatment to obtain a sample after hydrothermal aging treatment, and then the NH3-SCR performance is measured to evaluate its hydrothermal stability. The specific process is: the Cu-SSZ-13 molecular sieve of Comparative Example 1 is placed in a tubular furnace, air with a mass fraction of 10% H2O is continuously introduced, and hydrothermal aging treatment is performed at 750 ° C for 16 hours. The sample after hydrothermal aging is obtained.

[0054] Performance Testing: The molecular sieves obtained in Comparative Example 1 and Examples 1 to 9 were used in a gas-solid phase catalytic reaction fixed bed reactor to evaluate the catalytic activity of the catalyst for NH3-SCR reaction. Figure 5 The hydrothermal aged samples of Examples 11-12 and Comparative Example 2 were subjected to NH3-SCR reaction catalytic activity test to evaluate the hydrothermal stability of the prepared catalysts. The results are shown in Figure 6 The data of the catalytic activity test of the samples of Examples 1 to 9, Examples 11 to 12 and Comparative Examples 1 to 2 in the NH3-SCR reaction are recorded, and the data are shown in Table 2.

[0055] Table 2 NH3-SCR reaction performance of Examples 1-9, Examples 11-12 and Comparative Examples 1-2

[0056] From the data in Table 2, it can be seen that the samples obtained by using Examples 1 to 9 have very high catalytic performance, low temperature activity (175°C), high temperature activity (475°C) and T 90 Temperature window width (NOx The conversion rate is more than 90%) and is better than that of Comparative Example 1. It shows that the Cu-SSZ-13 molecular sieve prepared after adding vitamin C modification has very high low / high temperature catalytic activity and temperature window, and the catalytic activity is improved compared with the traditional Cu-SSZ-13. As can be seen from Table 2, after hydrothermal aging, the samples of Examples 11 to 12 still have very high catalytic activity, and the catalytic performance is better than that of the sample of Comparative Example 2. It shows that the Cu-SSZ-13 molecular sieve prepared after adding vitamin C modification has very high resistance to hydrothermal aging, and is improved compared with the traditional Cu-SSZ-13.

[0057] The molecular sieves obtained in Comparative Example 1 and Examples 1-2 were tested in an atmosphere containing 100 ppm SO2 to evaluate the NH3-SCR catalytic activity. The results are as follows: Figure 7 As shown. Figure 7 It can be concluded that after SO2 is applied, the catalytic activity of the samples in Examples 1 and 2 decreases significantly less than that of the samples in Comparative Example 1, and the catalytic activity recovers rapidly after the SO2 gas is removed. However, after SO2 is applied, the activity of the samples in Comparative Example 1 decreases greatly and cannot recover rapidly. This indicates that the Cu-SSZ-13 molecular sieve prepared after modification with the addition of vitamin C has a very high resistance to sulfur poisoning, and is improved compared to the traditional Cu-SSZ-13.

[0058] In conclusion, the Cu-SSZ-13 molecular sieve prepared by adding vitamin C modification has very high low-temperature and high-temperature catalytic activity, a wide T 90 The temperature window is narrower and the catalytic performance is improved compared to the traditional Cu-SSZ-13, and it has very high hydrothermal stability and resistance to sulfur poisoning.

[0059] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing Cu-SSZ-13 molecular sieve, characterized in that: The following steps are involved: (1) mixing an aluminum source, a silicon source, an inorganic base, an organic structure directing agent, water and vitamin C in sequence to form a gel, wherein the molar ratio of the aluminum source, the silicon source, the inorganic base, the organic structure directing agent, water and vitamin C is 1: 30-50: 15-18: 3-10: 500-1500: 0.3-5, stirring the gel for a period of time at room temperature, and performing an aging treatment to obtain an aged gel; (2) placing the aged gel in an autoclave for continuous crystallization for a period of time to obtain a crystallized product; The crystallized product is filtered, washed, dried and calcined to obtain SSZ-13 molecular sieve; (3) The SSZ-13 molecular sieve obtained in the previous step is subjected to ion exchange with copper salt, washed, dried and calcined to obtain a finished product.

2. The method for preparing Cu-SSZ-13 molecular sieve according to claim 1, characterized in that: The silicon source is selected from at least one of tetraethyl silicate, silica sol and white carbon black; the aluminum source is selected from at least one of aluminum oxide, aluminum hydroxide, aluminum sulfate and aluminum nitrate; the inorganic base is selected from sodium hydroxide; the organic structure directing agent is N,N,N-trimethyladamantane ammonium hydroxide, the copper salt is at least one of copper nitrate, copper acetate and copper sulfate; and the vitamin C is more than 95% by mass of Vc.

3. The method for preparing Cu-SSZ-13 molecular sieve according to claim 1, characterized in that: The aging temperature is 10-40° C., and the aging time is 3-8 hours.

4. The method for preparing Cu-SSZ-13 molecular sieve according to claim 1, characterized in that: The crystallization temperature is 110-170° C., and the crystallization time is 3-7 days.

5. The method for preparing Cu-SSZ-13 molecular sieve according to claim 1, characterized in that: The drying temperature is 80~150℃ and the drying time is 8~16 hours.

6. The method for preparing Cu-SSZ-13 molecular sieve according to claim 1 or 5, characterized in that: The calcination temperature is between 300 and 700°C, and the calcination time is between 2 and 10 hours.

7. The method for preparing Cu-SSZ-13 molecular sieve according to claim 1 or 2, characterized in that: The ion exchange temperature is 25-85° C., and the copper salt concentration is 0.002-0.2 mol / L.

8. Use of the finished product prepared by the Cu-SSZ-13 molecular sieve preparation method as claimed in any one of claims 1 to 7 in NH3-SCR catalytic reaction.

Citation Information

Patent Citations

  • Preparation method of antibacterial and deodorant material for refrigerator and freezer

    CN106139216A

  • Nano-level zero-valent iron carrier as well as preparation method and application thereof

    CN107243358A

  • Preparation method of catalyst for improving denitration performance of metal modified SSZ-13

    CN117019214A

  • SCR catalysts having improved low temperature performance, and methods of making and using the same

    US20150246345A1